Developing Transparent Concrete Geometry Media Using the 4D Model for Junior High School Surface Area Learning - Juwita Kirana Wulandari; Jennya Zahra Aristi; Adelia Putri; Dinar Nirmalasari (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aims to develop transparent concrete learning media for spatial geometry and evaluate its feasibility, practicality, and effectiveness in supporting students’ understanding of surface area concepts. This development applies the 4D model (Definition, Design, Development, and Dissemination) and involves one media expert, one subject matter expert, and 30 ninth-grade students during the limited dissemination phase. The uniqueness of this study lies in the use of a transparent acrylic model that allows students to clearly observe the relationships among planes, edges, and angles, providing a concrete, visually accessible representation of geometric structures. The research procedure included a student needs analysis, prototype design and production, product validation through expert review, and limited classroom deployment supported by pre- and post-test assessments. Media experts rated the product at 80% (acceptable), while subject matter experts rated it at 87.5% (highly acceptable). Students’ conceptual understanding improved significantly, with the average pre-test score of 81.43 increasing to 100 on the post-test, resulting in an N-Gain of 1.00 (very high). The student response rate reached 66.9% (very practical). These findings indicate that transparent concrete geometric media are feasible, practical, and effective, offering pedagogical advantages for enhancing students’ conceptual understanding through realistic, transparent geometric representations.